Early Breastfeeding Initiation, Caesarean Section, And Pre-Lacteal Feeding Practices - Rachma Purwanti; Mentari Suci Ramadini Sujono (poltekkes kemenkes mataram, 2023)
Pre-lacteal feeding practices prevalence in Indonesia was 45%. This study's objective was to analyze factors that correlate with pre-lacteal feeding practices in Kedungsari Village, Tarokan District, Kediri Regency. This study was a cross-sectional design with 104 subjects. The subject recruited by total sampling technique was a mother of 6 – 24month-old children who came to Integrated Health Pos (Posyandu) in Kedungsari Village in January 2022. The variables studied included pre-lacteal feeding practices, socio-demographic factors, and birth-related factors. Data analyzed were univariate, bivariate, and multivariate. The bivariate analysis used the Kendall Tau b correlation test, while the multivariate analysis used the multiple logistic regression test. Pre-lacteal feeding practices prevalence among those under 24 months old in Kedungsari Village was 44.2%. History of caesarean section delivery was a risk factor of pre-lacteal feeding practices (p=0.029 and 95%CI=1.140 – 12.226). Early breastfeeding initiation was a protective factor of pre-lacteal feeding practices (p=0.036 and 95%CI= 0.093 – 0.921). Only 20.9% of pre-lacteal feeding practices can be predicted by early breastfeeding initiation and history of cesarean delivery, while 79.1% other predicted by factors outside this study. Further research is needed to analyze other factors that contributed to pre-lacteal feeding practices in Kedungsari Village.